Hacer investigación en la universidad: ¿una profesión naciente?" / University research : a rising profession? (2010)
This paper argues for the thesis research plan at the university as a process of structural differentiation of roles within the concept of academic professionalism. The teaching concept has expanded its con- tents beyond its assumptions, facing ambiguities and displacements that satisfy neither organizations nor the expected role. Differentiation is an indicator of a new profession that emerges from require ments linked to the globalization of knowledge and that has only recently settled in Latin America and particularly in Colombia. This document broadly reconstructs the process followed by research at the Universidad Cooperativa de Colombia during the last 20 years. It also portrays the limitations and opportunities and suggests a path to be followed collectively and institutionally.